2004
DOI: 10.15288/jsa.2004.65.204
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent heavy episodic drinking trajectories and health in young adulthood.

Abstract: ABSTRACT. Objective: This study examined the association of trajectories of heavy episodic drinking (at least five alcoholic drinks on one occasion) during adolescence with health status and practices at age 24. Method: Semiparametric group-based modeling and logistic regressions were used to analyze data from a longitudinal panel of 808 youths interviewed between 10 and 24 years of age. Results: Four distinct trajectories of adolescent heavy episodic drinking were identified: nonheavy drinkers, late onsetters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 35 publications
7
134
2
4
Order By: Relevance
“…Stud. Alcohol Drugs 69: [866][867][868][869][870][871][872][873][874][875][876][877]2008) N UMEROUS STUDIES HAVE EXAMINED changes in volume and pattern of drinking over the life course, with most focusing on the heavy drinking trajectories from adolescence to early adulthood (Chassin et al, 2002;Hill et al, 2000;Oesterle et al, 2004;Schulenberg et al, 1996;Tucker et al, 2003;Windle et al, 2005). Within the developmental framework of this rich literature, numerous factors have discriminated among different drinking trajectories.…”
Section: Three-year Changes In Adult Risk Drinking Behavior Inmentioning
confidence: 99%
“…Stud. Alcohol Drugs 69: [866][867][868][869][870][871][872][873][874][875][876][877]2008) N UMEROUS STUDIES HAVE EXAMINED changes in volume and pattern of drinking over the life course, with most focusing on the heavy drinking trajectories from adolescence to early adulthood (Chassin et al, 2002;Hill et al, 2000;Oesterle et al, 2004;Schulenberg et al, 1996;Tucker et al, 2003;Windle et al, 2005). Within the developmental framework of this rich literature, numerous factors have discriminated among different drinking trajectories.…”
Section: Three-year Changes In Adult Risk Drinking Behavior Inmentioning
confidence: 99%
“…In an 8-year follow-up of Canadian adults 18-64 years of age, Murray et al (2002) found that having ever consumed 8+ drinks in a single day during the year preceding baseline was associated with increased risks of coronary heart disease and hypertension among men and of coronary heart disease among women. Oesterle et al (2004) reported that adolescents who engaged in chronic heavy drinking had increased risks of overweight, obesity and high blood pressure at age 24. In contrast, Steffens et al (2006) failed to find an association between risk drinking (5+/4+) at baseline and incidence of hypertension in a sample of adults followed for an average of 5.6 years, and Haynes et al (2005) reported no association between baseline risk drinking and the incidence of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Moffitt is ignoring a substantial proportion of adult offenders for whom she estimates no career trajectories. Many prior studies suffer this same limitation of focusing solely on juvenile careers (Nagin and Tremblay, 1999;Fergusson, et al, 2000;Maughan, et al, 2000;Colder, et al, 2001;Brame et al, 2001a;Nagin and Tremblay, 2001a;Nagin and Tremblay, 2001b;Brame et al, 2001b;Li, et al, 2001;Cote, et al, 2001;Cote, et al, 2002;Colder, et al, 2002;Lacourse et al, 2002;Chung, et al, 2002a;Guo, et al, 2002;Lacourse, et al, 2003;Broidy, et al, 2003;Mustillo, et al, 2003;Schaeffer, et al, 2003;Nagin, et al, 2003;Wiesner and Silbereisen, 2003;Oesterle, et al, 2004;Tremblay, et al, 2004;Hix-Small, et al, 2004;Wiesner and Windle, 2004;Bongers, et al, 2004;Brame, et al, 2005;. Moreover, Piquero and Brezina (2001) have disputed many of the reasons for adolescence-limited offending and found that, rather than being a specific cause for delinquency, the desire for autonomy is actually rather general, which is inconsistent with Moffitt's premise (1993).…”
Section: Critique Of Prior Researchmentioning
confidence: 99%